The α2δ-like Protein Cachd1 Increases N-type Calcium Currents and Cell Surface Expression and Competes with α2δ-1 - Shehrazade Dahimene (Cell Reports, 2018)
Summary: Voltage-gated calcium channel auxiliary α2δ subunits are important for channel trafficking and function. Here, we compare the effects of α2δ-1 and an α2δ-like protein called Cachd1 on neuronal N-type (CaV2.2) channels, which are important in neurotransmission. Previous structural studies show the α2δ-1 VWA domain interacting with the first loop in CaV1.1 domain-I via its metal ion-dependent adhesion site (MIDAS) motif and additional Cache domain interactions. Cachd1 has a disrupted MIDAS motif. However, Cachd1 increases CaV2.2 currents substantially (although less than α2δ-1) and increases CaV2.2 cell surface expression by reducing endocytosis. Although the effects of α2δ-1 are abolished by mutation of Asp122 in CaV2.2 domain-I, which mediates interaction with its VWA domain, the Cachd1 responses are unaffected. Furthermore, Cachd1 co-immunoprecipitates with CaV2.2 and inhibits co-immunoprecipitation of α2δ-1 by CaV2.2. Cachd1 also competes with α2δ-1 for effects on trafficking. Thus, Cachd1 influences both CaV2.2 trafficking and function and can inhibit responses to α2δ-1. : Dahimene et al. examine the role of Cachd1, a protein with similarity to the auxiliary α2δ subunits of voltage-gated calcium channels. They find that Cachd1 increases N-type calcium currents substantially despite having a disrupted VWA interaction domain. Cachd1 also enhances channel trafficking and inhibits responses to α2δ-1. Keywords: voltage-gated calcium channel, Cachd1, cell surface expression, interaction site, cache domain